Mobilitas Uranium pada Endapan Sedimen Sungai Aktif di Daerah Mamuju, Sulawesi Barat - Mu’awanah, Frida Rosidatul; Priadi, Bambang; Widodo; Sukadana, I Gde; Andriansyah, Rian (BRIN Publishing, 2018)
Mamuju is an area that has a high dose rate (radioactivity) value. The research area consists of 6 sectors namely Ahu, Orobatu, Takandeang, Botteng, Pangasaan, and Taan Sector. Lithological distribution does not represent the distribution of uranium; therefore geochemical method is needed to observe the distribution of uranium in the drainage system. The aim of this research is to provide an overview of the mobility and distribution of uranium in the drainage system using stream sediment. Uranium mobility analysis uses labile percent obtained from the ratio of total uranium and labile uranium, the total uranium value obtained from the measurement of X-Ray fluorescence spectrometry and the value of labile uranium obtained from measurement of labile fluorimetry. The sample taken from 4 potential areas based on radiometric value Map. The result of analysis shows that Ahu Sector has labile uranium anomaly >113.44 ppm, Pangasaan Sector with labile uranium anomaly >168.63 ppm, Takandeang Sector with uranium labile anomaly values >74.36 ppm, and Botteng Sector with uranium labile anomaly >84.23 ppm. The anomaly types identified from two sectors, namely Ahu Sector anomaly is related to the precipitation of dissolved uranium hydrolysates in stream deposit originating from Ahu lava and Tapalang breccia, while Takandeang Sector anomaly is related to the enrichment of in situ uranium in soil and Takandeang lava.